Perlindungan Hukum terhadap Korban Penganiayaan yang Dilakukan oleh Oknum Polri Saat Aksi Demonstrasi - Arnold Sotarduga Silangit; Laili Furqoni; Fanny Tanuwijaya (Program Pasca Sarjana Unej, 2022)
This study aims to analyze the legal rules governing legal protection for victims of repressive actions carried out by police officers when securing demonstrations or what are commonly called rallies. The right to express opinions is a human right that is guaranteed in Article 28 of the 1945 Constitution of the Republic of Indonesia. In the implementation of demonstrations that result in casualties, it is clear that there is an error or a form of violation, including Human Rights which are clearly regulated in the Constitution. some pre-existing rules. This study uses a juridical-normative method with a conceptual approach and legislation. The authors in this study used primary legal materials derived from legislation and secondary sources from legal books and journals that were relevant to the discussion. Then to enrich the references in this study, the authors use non-legal materials. This research shows that, there has been legal protection that has been provided by the Government in the form of preventive and repressive protection and the existence of PROPAM is considered helpful in protecting the rights of the community. Keywords: Legal Protection, Repressive Action, Demonstration